Preparation and Photochemistry of Hydroxy Isocyanate - Guohai Deng; Justus Liebig University Giessen (My University, 2025)
We describe the first spectroscopic identification of hitherto experimentally unreported hydroxy isocyanate HONCO, a potential candidate for the interstellar medium and prebiotic chemistry. This planar chain molecule was prepared in the gas phase through flash vacuum pyrolysis of phenyl N-hydroxycarbamate at 650 °C and was subsequently trapped in argon matrices at 3.5 K. Its characterization was accomplished by means of matrix isolation IR and UV/Vis spectroscopy together with quantum chemical calculations. Upon the UV light (λ = 313 nm) irradiation, HONCO decomposes into hydrogen-bonded complexes of HON and HNO with CO. The names of the files refer to the following article: https://doi.org/10.26434/chemrxiv-2025-dz83j
Keywords: Isocyanate; Matrix-isolation; Photochemistry; Prebiotic molecules; Pyrolysis; ddc:540